Analysis of exchange-rate regime effect on growth: theoretical channels and empirical evidence with panel data - Marjan Petreski (Kiel Institute for the World Economy (IfW), 2009)
The aim of this paper is to empirically investigate the relationship between exchange-rate regime and economic growth, building on underlying theoretical examination and shortcomings of empirical literature. Channels through which regime might influence growth could be distinguished at: i) level of uncertainty imposed by certain regime, which than affects trading and investment decisions; ii) regime as shock absorber; iii) its linkage to productivity growth, which usually interferes with financial development. Empirical research offers divergent result though and is criticized because of: measurement error in regimes' classification; appropriateness of growth framework; endogeneity of exchange-rate regime and/or other regressors; Lucas critique; sample-selection bias and survivor bias. Applying dynamic system-GMM panel estimation on 169 countries over the period 1976-2006 and addressing all shortcoming of the empirical literature, this paper finds that the exchange-rate regime is not statistically significant in explaining growth. The conclusion is robust to dividing the sample on developing versus advanced countries and considering two sub-periods. In all specifications, the exchange-rate regime does not even approach conventional significance levels. Observation de-facto versus de-jure regime matters neither. No empirical grounds were established that coefficients in the regression suffer the Lucas critique. Hence, the main conclusion is that, as nominal variable, the exchange rate regime does not have explanatory power over growth.
Keywords: E42; F31; 330; Exchange rate regime; economic growth; Wechselkurssystem; Wirtschaftswachstum; Panel; Schätzung; Anlageverhalten